Biological control of strawberry soil-borne pathogens Macrophomina phaseolina and Fusarium solani, using Trichoderma asperellum and Bacillus spp. - PASTRANA, Ana; BASALLOTE-UREBA, María; AGUADO, Ana; AKDI, Khalid; CAPOTE, Nieves (Phytopathologia Mediterranea, 2016)
In south-western Spain, Macrophomina phaseolina and Fusarium solani were found to be associated in strawberry plants with, respectively, charcoal rot, and crown and root rot symptoms. For management of both fungal diseases, the antagonistic effects of two commercial formulations, one based on Trichoderma asperellum T18 strain (Prodigy®) and the other on Bacillus megaterium and B. laterosporus (Fusbact®), were evaluated in vitro and under controlled environment and field conditions. Two inoculation methods (root-dipping and soil application) and two application times (pre- and post-pathogen inoculation, as preventive and curative treatments, respectively) were assessed. Dual plate confrontation experiments demonstrated the antagonistic effects of T. asperellum and Bacillus spp. by inhibiting radial growth of M. phaseolina and F. solani by more than 36%. Preventive application of T. asperellum by root-dipping reduced the incidence of charcoal rot (up to 44% in a growth chamber and up to 65% under field conditions) and also reduced disease progression, the percentage of crown necrosis, as well as the level of infection measured as ng of pathogen DNA g-1 plant by quantitative real-time PCR. This treatment was also the most effective for reduction of crown and root rot caused by F. solani (up to 100% in a greenhouse and up to 81% under field conditions). These results were nearly comparable with the control achieved using chemical fungicides. The Bacillus spp.-based formulation was also effective for control of charcoal rot and showed variable results for control of F. solani, depending on the growth conditions.